2004
DOI: 10.1159/000081595
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele and Retrograde Adrenal Metabolites Flow

Abstract: Background: Idiopathic varicocele is one of the causes of potentially correctable male subfertility. The mechanisms causing spermatogenesis impairment have yet to be clarified. The aim of this study is to analyze the effects of renal and adrenal metabolite reflux on testicular exocrine function in a rat experimental model. Materials and Methods: In the study, 45 male Lewis Stock adult rats, each weighing 300 g, were used. The rats were subdivided into three groups of 15 rats. In group A (control group) testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…One concern about delayed surgical correction is that the testicular lesions caused by varicocoele, independent of patient age, are potentially irreversible (Sigman & Jarow, 1997;Camoglio et al, 2004). On the contrary, many studies have described significant improvement in semen quality after varicocoelectomy in both adults and adolescents (Dubin & Amelar, 1970;Lewis & Harrison, 1982;Chehval & Purcell, 1992;Paduch & Niedzielski, 1997).…”
Section: To Treat or Not?mentioning
confidence: 99%
“…One concern about delayed surgical correction is that the testicular lesions caused by varicocoele, independent of patient age, are potentially irreversible (Sigman & Jarow, 1997;Camoglio et al, 2004). On the contrary, many studies have described significant improvement in semen quality after varicocoelectomy in both adults and adolescents (Dubin & Amelar, 1970;Lewis & Harrison, 1982;Chehval & Purcell, 1992;Paduch & Niedzielski, 1997).…”
Section: To Treat or Not?mentioning
confidence: 99%
“…Theories related to the negative effect of varicocele on testicular functions include testicular hyperthermia, hormonal dysfunctions, increased testicular blood flow due to venous engorgement, reflux of renal or perirenal metabolites, and hypoxia [2–4]. Weiss et al [5] reported impaired testosterone synthesis in patients with varicocele.…”
Section: Introductionmentioning
confidence: 99%
“…43 Reflux of blood down the testicular vein has been demonstrated in patients with varicoceles. 44,45 Abnormal blood flow It is postulated that increased blood flow to the testicle may lead to increased hydrostatic pressure and change in the composition of the interstitial fluid.…”
Section: Proposed Mechanism Detailsmentioning
confidence: 99%